Analysis Of The Influence Of Digital Economy Factors On Gross Domestic Product in Indonesia - Andika Syahputra; Wahyu Indah Sari; Bakhtiar Efendi (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2023)
Economic growth in Indonesia has become a major focus for the government and other stakeholders. As one of the most populous countries in the world and an active member of the Southeast Asian economic region, Indonesia has great potential to achieve high and sustainable economic growth. This study uses a quantitative approach. The quantitative method is a research method that can be interpreted as a research method based on the philosophy of positivism, used for research on certain populations or samples, data collection using research instruments, quantitative data analysis with the aim of testing the established hypothesis. This research is associative (relationship), namely a research method that aims to determine the relationship between two or more variables, where this study aims to determine the relationship between the influence of independent variables on the dependent variable. With this research, a theory can be built that can function to explain, predict and control a symptom. Based on the results of data processing output using the SPSS 22 data processing application, the variables of internet users, the level of e-commerce users and the level of digital payments have an effect on GDP through the results of the t-test and f-test. Based on the formulation of the problem and the results of the tests that have been carried out, the following conclusions can be drawn: A. Exports have a positive and significant effect on Indonesia's Foreign Exchange Reserves where t count (2.305) t table (1.74) and significant (0.035) (0.05).